Perspectives of (/memorandum for) systems thinking on COVID‐19 pandemic and pathology. Issue 3 (28th September 2022) - Tretter, Felix; Peters, Eva M. J.; Sturmberg, Joachim; Bennett, Jeanette; Voit, Eberhard; Dietrich, Johannes W.; Smith, Gary; Weckwerth, Wolfram; Grossman, Zvi; Wolkenhauer, Olaf; Marcum, James A.
Abstract: Is data‐driven analysis sufficient for understanding the COVID‐19 pandemic and for justifying public health regulations? In this paper, we argue that such analysis is insufficient. Rather what is needed is the identification and implementation of over‐arching hypothesis‐related and/or theory‐based rationales to conduct effective SARS‐CoV2/COVID‐19 (Corona) research. To that end, we analyse and compare several published recommendations for conceptual and methodological frameworks in medical research (e.g., public health, preventive medicine and health promotion) to current research approaches in medical Corona research. Although there were several efforts published in the literature to develop integrative conceptual frameworks before the COVID‐19 pandemic, such as social ecology for public health issues and systems thinking in health care, only a few attempts to utilize these concepts can be found in medical Corona research. For this reason, we propose nested and integrative systemic modelling approaches to understand Corona pandemic and Corona pathology . We conclude that institutional efforts for knowledge integration and systemic thinking, but also for integrated science, are urgently needed to avoid or mitigate future pandemics and to resolve infection pathology.